CTA will distribute catalogue to ACP countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
CTA has agreed to buy 100 copies of the printed union catalogue of serials in 14 International Agricultural Research Centres (lARCs), for distribution in the ACP countries. The catalogue is the result of work done by L J Haravu, former Information...